Field study of parasitic contamination of fruits, vegetables and leafy greens in the Ecuadorian Andes [version 1; peer review: 2 approved, 1 approved with reservations] - María Trelis; Màrius Vicent Fuentes; Cecilia Alejandra García Ríos; Julio César Carrero; Pablo Djabayan-Djibeyan; José G. Prato; Luisa Carolina González-Ramírez (F1000Research, 2023)
Background: Raw vegetables have been considered vehicles of enteroparasites. South American countries are among the most important exporters of fresh vegetables; Ecuador has tropical climates and soils rich in organic matter that allow it to harvest throughout the year for sale to different countries. The aim of the study was to assess the occurrence of the parasitic contamination of fruits, vegetables and leafy greens grown in an agricultural area of the Ecuadorian Andes. Methods: A field study, cross-sectional, snowball sampling was conducted on 1,416 samples (516 fruits, 488 vegetables, and 412 leafy greens). Each sample were washed with water, and the resulting solution after removing the vegetables, was subjected to 24-hour sedimentation. The concentrated sediment underwent microscopic analysis. Results: Parasites were detected in 63.4% of the samples, leafy greens were the most contaminated (76.9%) (P<0.0001), (vegetables 67.8% and fruit 48.4%), of these, cabbage (100%), onions (84%) and strawberries (60.2%) were the most contaminated. Protozoa were more frequent (49.6%) than helminths (15.5%) (P<0.0001). Blastocystis sp. (33.5%) was the highest, followed by Eimeria spp. (26.3%), Entamoeba spp. (10.3%), Giardia spp. (8.3%), Balantidium spp. (6.9%); Cryptosporidium spp. (6.6%), Cyclospora spp. (4.4%), Cystoisospora spp. (0.5%); Strongylida (15.5%) and Ascaris spp. (0.4%). Conclusion: The consumption of fruits, vegetables, and leafy greens from these crops is a possible source of infection to humans and animals in this area or in nonendemic areas where these products are marketed. This study establishes the need for strict hygienic measures in growing; this will be properly achieved by the treatment of the soil, manure and water used for cultivation.